Implementation of talent management policy in the North Sulawesi provincial government - Treviani Emma Engel Walangitan; Wirman Syafri; Rizki Amalia (Sean Institute, 2024)
The focus of this research is to find out the implementation of talent management policies in the North Sulawesi Provincial Government and what efforts have been made to overcome obstacles to implementing talent management policies. Researchers use the theory by Edwards III regarding policy implementation with four dimensions, namely communication, resources, disposition and bureaucratic structure. This research uses qualitative research methods with a descriptive approach. The data collection techniques used were observation, interviews, documentation. The data analysis used is data reduction, data presentation and drawing conclusions. The results of this research show that the implementation of talent management policies in the North Sulawesi Provincial Government has not gone well, which can be seen in the communication dimension which has not been optimal, there has been no socialization of talent management policies to employees, in the resource dimension there are still obstacles, namely inadequate human resources in the form of a lack of implementing staff tasked with facilitating employee potential and competency assessment activities, and do not have assessors, and do not have a technology-based talent management information system. In the organizational structure dimension, obstacles were encountered, namely that standard operational procedures were not yet available, while in the implementation attitude (disposition) dimension, things were going quite well, as can be seen from the commitment of regional leaders through competency development in the form of education and training as well as providing learning tasks for employees.